GEOPHASE ANALYSIS OF GEOECOLOGICAL CHANGES CAUSED BY CLIMATE CHANGE IN THE KHOREZM REGION - Aminov, B.B. (SCIENCE and SOCIETY, 2025)
The article presents a geospatial analysis of geoecological changes in the Khorezm region as a result of climate change. The article geospatial analysis of the main geoecological indicators in the Khorezm region, such as temperature, precipitation, soil moisture, groundwater level, desertification processes, and changes in vegetation cover, is carried out in the period 2000-2023. Based on space images, GIS technologies, and monitoring data of important geoecological indicators, the ecological situation in various districts of the region is monitored and analyzed.